2013
DOI: 10.1002/celc.201300047
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Reduction Reaction Studies of Phosphorus and Nitrogen Co‐Doped Mesoporous Carbon Synthesized via Microwave Technique

Abstract: Metal‐free mesoporous P and N co‐doped carbon (PNDC) composites are evaluated for their electrocatalytic activity towards the oxygen reduction reaction (ORR). Carbonization of melamine and hexamine‐modified tannin in the presence of polyphosophoric acid produces PNDCs with prominent oxygen reduction properties in alkaline media. The effect of the P and N content in the carbon material is evaluated in terms of the ORR activity. The compound containing a high amount of N (8.3 atom %) and P (6.8 atom %), denoted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 55 publications
0
44
0
Order By: Relevance
“…M–N–C catalysts show excellent performance for the ORR, owing to their specific metal–nitrogen (M–N) bonds, which play crucial roles in oxygen reduction . Unfortunately, recent research on M–N–C catalysts has mainly been focused on the pyrolysis of the carbon materials with nitrogen sources and metal salts (nitrates or chlorides) . These methods always suffer from complicated preparation methods, uncontrollable generation of the metal oxides, and agglomeration of the metal nitrides in the carbon matrix.…”
Section: Introductionmentioning
confidence: 99%
“…M–N–C catalysts show excellent performance for the ORR, owing to their specific metal–nitrogen (M–N) bonds, which play crucial roles in oxygen reduction . Unfortunately, recent research on M–N–C catalysts has mainly been focused on the pyrolysis of the carbon materials with nitrogen sources and metal salts (nitrates or chlorides) . These methods always suffer from complicated preparation methods, uncontrollable generation of the metal oxides, and agglomeration of the metal nitrides in the carbon matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, additional reports have revealed that the incorporation of two or more types heteroelement dopants into carbon materials could create large numbers of active sites favorable for electrocatalysis . In fact, some of these bi‐ and tridoped carbon materials (for example, N and S; B and N; or N and P co‐doped carbons) show better catalytic performances toward ORR than their singly‐doped counterparts, and in some cases, better activities than even Pt/C (20 %) . They also often show much better stability than Pt/C catalysts .…”
Section: Heteroatom‐doped Carbon Electrocatalysts and Their Synthesimentioning
confidence: 99%
“…As mentioned above, carbon materials doped with multiple types of dopants (e.g., N and B; N and P; N and S; N, P and S; etc.) often show high electrocatalytic activities ,. Synthetic methods that can provide multi‐doped carbon materials with not only high dopant density but also uniformly distributed multi‐element dopants are, however, lacking.…”
Section: Challenges To Address and Perspectivesmentioning
confidence: 99%
“…[4] In view of this, extensive research efforts have been carried out to overcome these problems, including the synthesis of noble-metal/transition-metal (such as Fe, Co, Cu, and Ni)a lloys with special structuralc ontrol [4a, 5] and entirely new non-noble-metal materials doped with the active elements, such as metal-free heteroatom-doped carbon materials, [1c, 6] transition-metal/nitrogen-doping carbon materials (M-N x -C), [7] transition-metal nitrides, [8] oxides, [9] and sulfides, [10] as well as their hybrids, [7b, 11] etc. [12] The major one is the thermal treatment strategy of precursors with the help of as ol-gel technique, [13] the template method, [14] and in situ synthesis [15] .T he second aspectf ocuseso nn ew strategies, involving chemical vapor deposition, [16] the wet-chemical strategy, [17] microwave methods, [18] etc. [12] The major one is the thermal treatment strategy of precursors with the help of as ol-gel technique, [13] the template method, [14] and in situ synthesis [15] .T he second aspectf ocuseso nn ew strategies, involving chemical vapor deposition, [16] the wet-chemical strategy, [17] microwave methods, [18] etc.…”
Section: Introductionmentioning
confidence: 99%